PENGAMATAN KONDISI FISIK LAHAN GAMBUT UNTUK MEMPERKUAT MITIGASI BENCANA KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU - M. Bayu Rizky Prayoga; Mahawan Karuniasa; Evi Frimawaty (EnviroScienteae, 2022)
Forest fire in Indonesia is a cataclysmic event that routinely happens consistently every year. The Indonesian government's intervention in suppressing forest fires is often carried out when massive fires have already occurred massively. When it happens in peat soil, forest fires become hard to extinguish because of the characteristics of burning below the ground surface, better known as the phenomenon of peat smoldering. Thus, that condition challenges the mitigation of forest fires in Indonesia to prioritize preventive principles in its implementation, one of which is through observing the physical condition of peatlands. This study examines and identifies existing regulations and policies concerning forest fires disaster mitigation by taking Riau Province as study area, one of Indonesia's areas that are, in many cases, hit by forest fires annually. Through the analysis of literature studies of relevant sources, this paper seeks to provide input on how monitoring the physical condition of peatlands can support decision-making related to forest fires disaster mitigation activities. This study explains that policies and regulations concerning the mitigation of forest fire in Indonesia still have not considered the scientific basis of the peatland physical parameters for mitigation activities, especially in determining disaster status level, which has further implications for the effectiveness of forest fires suppression activities. Furthermore, this study also highlights that by monitoring peatlands' physical condition, peatlands can be implemented to improve the paradigm in overcoming forest fires in Indonesia to be more preventive and succesful.